Efektivitas Media Teknologi Untuk Meningkatkan Pemahaman Peserta Didik Dalam Pembelajaran - Latsa Alya Utami; Yusril Muhamad Anjar; Unik Hanifah Salsabila; Hesti Hesti (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi NW Pancor, 2022)
Abstract This article was created to find out how the effectiveness of educational technology is applied to improve students' understanding and to find out how to use educational technology in Islamic religious education. The method used is using a qualitative method in which in writing this journal we conduct interviews with resource persons to collect data as material for journal articles. From this article, it can be concluded that in the learning process, educational technology is needed in order to achieve educational goals, namely developing the potential of students. In Islamic religious education, it is also recommended to use educational technology so that science in its development can be based on the Qur'an and Sunnah. Keywords : Educational Technology, Effectiveness, Utilization Abstrak Artikel ini dibuat untuk mengetahui bagaimana keefektifan teknologi pendidikan yang diterapkan untuk meningkatkan pemahaman peserta didik dan mengetahui bagaimana pemanfaatan teknologi pendidikan dalam pendidikan agama islam. Metode yang digunakan yaitu menggunakan metode kualitatif yang mana dalam penulisan jurnal ini kami melakukan wawancara kepada narasumber guna menggumpulkan data sebagai bahan artikel jurnal. Dari artikel ini dapat disimpulkan bahwa dalam proses pembelajaran sangat dibutuhkan teknologi pendidikan agar dapat tencapai tujuan pendidikan yaitu mengembangkan potensi peserta didik. Dalam pendidikan agama islam juga menganjurkan untuk menggunakan teknologi pendidikan agar ilmu pengetahuan dalam perkembangannya dapat berlandaskan pada Al-Qur'an dan As-sunah